The Influence of Motivation, Trust, Facilities, Job Stress, and Compensation on Employee Performance PT. Citra Lautan Teduh Batam - Desi, Velya Tri; Ratnasari, Sri Langgeng; Ismanto, Widodo (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine and analyze the influence of motivation, trust, facilities, work stress, and compensation on the performance of employees at PT Citra Lautan Teduh Batam. This research employs a quantitative approach, with data collected through questionnaires. The population in this study consists of all 84 employees of PT Citra Lautan Teduh Batam, and the sample of 84 respondents was determined using a census technique. The analysis results indicate that motivation has a positive and significant effect on employee performance; trust has a positive but not significant effect; facilities have a positive and significant effect; work stress has a positive and significant effect; and compensation has a positive and significant effect on employee performance. Overall, the findings show that the five variables motivation, trust, facilities, work stress, and compensation collectively influence employee performance.